IMPLEMENTASI MODEL PEMBELAJARAN BERDIFFERENSIASI PADA PEMBELAJARAN MATEMATIKA MATERI PECAHAN DI SMP N 1 BATAHAN - Siti Aisyah Hasibuan (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The independent curriculum emphasizes the importance of the level of readiness to develop learning strategies in accordance with students' learning achievement stages or what is also known as teaching at the right level (TaRL). This learning is carried out by providing varied learning materials according to the level of readiness of students. Educators need to know students' initial abilities before carrying out learning. To find out students' readiness, it is necessary to carry out an assessment at the beginning of learning or identify the results of the assessment from the previous meeting. Based on the results of the assessment at the beginning of learning, educators adjust learning to suit students' learning needs. We clearly know that the curriculum covers all subjects, one of which is mathematics. One important aspect of the independent curriculum is differentiated learning, which recognizes students' individual differences and provides learning experiences that suit their needs and interests. Differentiated learning is an approach that recognizes that each student has different needs and abilities. The main goal of differentiated learning is to ensure that each student can reach their maximum potential and feel motivated in the learning process by providing varied learning according to the students' learning needs.